A Highly Aligned Nanowire‐Based Strain Sensor for Ultrasensitive Monitoring of Subtle Human Motion. Issue 24 (10th May 2020) - Tang, Ning; Zhou, Cheng; Qu, Danyao; Fang, Ye; Zheng, Youbin; Hu, Wenwen; Jin, Ke; Wu, Weiwei; Duan, Xuexin; Haick, Hossam
Abstract: Achieving highly accurate responses to external stimuli during human motion is a considerable challenge for wearable devices. The present study leverages the intrinsically high surface‐to‐volume ratio as well as the mechanical robustness of nanostructures for obtaining highly‐sensitive detection of motion. To do so, highly‐aligned nanowires covering a large area were prepared by capillarity‐based mechanism. The nanowires exhibit a strain sensor with excellent gauge factor (≈35.8), capable of high responses to various subtle external stimuli (≤200 µm deformation). The wearable strain sensor exhibits also a rapid response rate (≈230 ms), mechanical stability (1000 cycles) and reproducibility, low hysteresis (<8.1%), and low power consumption (<35 µW). Moreover, it achieves a gauge factor almost five times that of microwire‐based sensors. The nanowire‐based strain sensor can be used to monitor and discriminate subtle movements of fingers, wrist, and throat swallowing accurately, enabling such movements to be integrated further into a miniaturized analyzer to create a wearable motion monitoring system for mobile healthcare. Abstract : A highly sensitive flexible strain sensor that is based on large‐area of aligned nanowires is developed. The sensor can be used as a wearable device to accurately detect, discriminate and monitor subtle movements linked with human motion.